Physical performance in elite male and female team-handball players - Wagner, H.; Fuchs, P.; Fusco, A.; Fuchs, P.; Bell, J. W.; von Duvillard, S. P. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Biological differences between men and women are well known; however, literature addressing knowledge about the influence of sex on specific and general performance in team handball is almost nonexistent. Consequently, the aim of the study was to assess and compare specific and general physical performance in male and female elite team-handball players, to determine if the differences are consequential for general compared with specific physical performance characteristics and the relationship between general and specific physical performance. Methods: Twelve male and 10 female elite team-handball players performed a game-based performance test, upper- and lower-body strength and power tests, a sprinting test, and an incremental treadmill running test. Results: Significant differences (P<.05) between male and female players were found for peak oxygen uptake and total running time during the treadmill test, 30-m sprinting time, leg-extension strength, trunk- and shoulder-rotation torque, and countermovement-jump height, as well as offense and defense time, ball velocity, and jump height in the game-based performance test. An interaction (sex×test) was found for time and oxygen uptake, and except shoulder-rotation torque and ball velocity in women, the authors found only a low relationship between specific and general physical performance. Conclusion: The results of the study revealed that male players are heavier, taller, faster, and stronger; jump higher; and have better aerobic performance. However, female players performed relatively better in the team-handball-specific tests than in the general tests. The findings also suggest that female players should focus more on strength training.